RELEVANSI METODE EKSPERIMEN TERHADAP PEMBENTUKAN SIKAP ILMIAH SISWA SEKOLAH DASAR - Elisabeth Irma Novinati Davidi; Kanisius Supardi; Martina Wahung (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2022)
The main purpose of this researches are to find out the relevance of the experimental method to increasing and to describe teacher’s efforts in applying the method in improving students’scientific attitudes scientific attitudes in elementary schools. This type of research was library research. Data wass collected by tracing and reviewing previous research journals, theses and books that were relevant to the research variabels. The results of the study showed that: (1) the application of the experimental method could improve students’scientific attitudes. This was shown by the changes in students scientific attitudes after using the exsperimental method in the learning process where there were improvement in students enthusiasm, self confidencec, courages in expressing their opinions during the learning process, (2) the teachers efforts in applying experimental methods to improving students scientivic attitudes were shown by giving the opportunities for students to be more actively, making the learning fun, and encourage the students to be involved directly in experimental learning, so that those efforts clou improve students scientific activities and attitudes.